Application of Bacillus sp. protease in the fabrication of silver/silver chloride nanoparticles in solution and cotton gauze bandages. (23rd November 2020) - Siritapetawee, Jaruwan; Limphirat, Wanwisa; Pakawanit, Phakkhananan; Phoovasawat, Chalermluck
Abstract: Silver (Ag)/silver chloride (AgCl) nanoparticles have been used worldwide for their antimicrobial activity. Proteases play an important role in many physiological processes during wound healing. Therefore, the aim of this study was to fabricate silver‐type nanoparticles exhibiting protease activity for medical applications such as wound healing and dressings. The Ag/AgCl nanoparticles were fabricated using Bacillus sp. protease and visible light activation. The size of the fabricated nanoparticles was estimated to be 35.29 ± 6.43 nm. The nanoparticles were coated on a cotton gauze bandage using immersion and ultrasonication. Scanning electron microscopy and energy dispersive X‐ray spectroscopy confirmed that the nanoparticles could be used to coat the gauze bandage. Synchrotron radiation X‐ray tomographic microscopy indicated that coating with the nanoparticles did not destroy the packing of cotton fibers in the gauze bandage. The nanoparticles exhibited fibrinolytic and collagenolytic activities. Protease activity remained after the nanoparticle coating was applied to the gauze bandage. The nanoparticles were not absorbed on a gelatin agar plate after incubation at 37 °C for 18 H. These results suggest that the coated cotton gauze bandage may be safe for further use, and the nanoparticles may not be absorbed into animal or human skin. Abstract : The Ag/AgCl nanoparticles were fabricated using Bacillus sp. protease and visible light activation. The nanoparticles were coated on a cotton gauze bandage using immersion and ultrasonication. Both the nanoparticles and the coated cotton gauze bandage exhibited fibrinolytic and collagenolytic activities.